THE EFFECTIVENESS OF USING EDUCATIONAL GAMES IN INDONESIAN LANGUAGE LEARNING IN ELEMENTARY SCHOOLS - Mas’ud Muhammadiyah; Ahmad Farrudin; Fransisca Debby Christine Fernandez; Napat Chai; Andi Hamsiah (International Journal of Educatio Elementaria and Psychologia, 2025)
Language learning in elementary schools plays a crucial role in developing students’ literacy, communication, and critical thinking skills. However, traditional teaching methods often fail to engage students effectively, leading to decreased motivation and suboptimal learning outcomes. This study investigates the effectiveness of using educational games as an innovative approach to enhance Indonesian language learning among elementary school students. A quasi-experimental research design with a pre-test and post-test control group was employed. The study involved 60 students, divided into an experimental group that used educational games and a control group that followed conventional learning methods. Data were collected using language proficiency tests, student motivation questionnaires, and teacher observations. These results indicate that educational games are effective in creating an interactive and enjoyable learning environment. The study concludes that incorporating educational games into language instruction can enhance learning outcomes and student motivation, providing valuable insights for teachers and curriculum developers.